Complementary Feeding Habits in Children Under the Age of 2 Years Living in the City of Adama in the Oromia Region in Central Ethiopia: Traditional Ethiopian Food Study - Gudeta, Adugna Negussie; Andrén Aronsson, Carin; Balcha, Taye Tolera; Agardh, Daniel (Frontiers in Nutrition, 2021)
Updated information on child feeding practices, nutritional status, and trends related to parental sociodemographic variables is required in developing countries. The objective of this study was to describe infant feeding practices and associated sociodemographic factors among Ethiopian children with an emphasis on complementary feeding. Information on infant feeding and anthropometric measures were obtained from 1054 mother-child pairs participating in a birth cohort study of children born between 2017 and 2020 prospectively followed in the city of Adama located in the Oromia region of central Ethiopia. Logistic regression models were used to identify sociodemographic and food groups associated with the initiation of complementary feeding. The introduction of the complementary foods at six months of age was 84.7% (95% CI, 82.5, 86.8). Vegetables, cereals (teff, wheat, barely), and fruits were most often the earliest types of foods introduced. Wasting, stunting, underweight, and low BMI by age were found in 6.0%, 16.9%, 2.5%, and 6.3%, respectively. Maternal age and occupation were factors associated with timely initiation of complementary feeding [OR=2.25, (95% CI, 1.14, 4.41)] and [OR=0.68, (95% CI], 0.48, 0.97)], respectively. This study demonstrates that the majority of Ethiopian children in the Oromia region follow the WHO recommendations on complementary feeding.